Translations of Developmental Screening Instruments: An Evidence Map of Available Research. Issue 6 (July 2015) - El-Behadli, Ana F.; Neger, Emily N.; Perrin, Ellen C.; Sheldrick, R. Christopher
ABSTRACT: Objective: Children whose parents do not speak English experience significant disparities in the identification of developmental delays and disorders; however, little is known about the availability and validity of translations of developmental screeners. The goal was to create a map of the scientific evidence regarding translations of the 9 Academy of Pediatrics–recommended screening instruments into languages other than English. Methods: The authors conducted a systematic search of Medline and PsycINFO, references of identified articles, publishers' Web sites, and official manuals. Through evidence mapping, a new methodology supported by AHRQ and the Cochrane Collaboration, the authors documented the extent and distribution of published evidence supporting translations of developmental screeners. Data extraction focused on 3 steps of the translation and validation process: (1) translation methods used, (2) collection of normative data in the target language, and (3) evidence for reliability and validity. Results: The authors identified 63 distinct translations among the 9 screeners, of which 44 had supporting evidence published in peer-reviewed sources. Of the 63 translations, 35 had at least some published evidence regarding translation methods used, 28 involving normative data, and 32 regarding reliability and/or construct validity. One-third of the translations found were of the Denver Developmental Screening Test. Specific methods used varied greatly across screeners, as did the level of detail with which results were reported. Conclusion: Few developmental screeners have been translated into many languages. Evidence map of the authors demonstrates considerable variation in both the amount and the comprehensiveness of information available about translated instruments. Informal guidelines exist for conducting translation of psychometric instruments but not for documentation of this process. The authors propose that uniform guidelines be established for reporting translation research in peer-reviewed journals, similar to those for clinical trials and studies of diagnostic accuracy. Abstract : This article has supplementary material on the web site: www.jdbp.org.